Optimization of fermentation parameters for bioethanol production from waste glycerol by microwave induced mutant Escherichia coli - Saifuddin N.; Refal H. (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2023)
bioethanol; chitosan; glycerol; agitation speed; anaerobic fermentation; Article; bacterial strain; biotransformation; concentration response; controlled study; Escherichia coli; immobilization; microwave radiation; nonhuman; nutrient concentration; organic nutrient; parameters; pH; statistical analysis; Taguchi statistical method; temperature